Glycosphingolipid synthesis is impaired in SLC35A2-CDG and improves with galactose supplementation - Andrea Jáñez Pedrayes; Sam De Craemer; Jakub Idkowiak; Dries Verdegem; Christian Thiel; Rita Barone; Mercedes Serrano; Tomáš Honzík; Eva Morava; Pieter Vermeersch; François Foulquier; Willy Morelle; et al. (Cellular and Molecular Life Sciences)
Abstract SLC35A2-CDG is an X-linked congenital disorder of glycosylation (CDG), characterized by defective UDP-galactose transport into the Golgi and endoplasmic reticulum and consequent insufficient galactosylation of glycans. Clinically, this translates into a range of predominantly neurological symptoms. Although the pathomechanism of this disorder is not fully understood, oral galactose supplementation has led to clinical and biochemical improvement in some patients. Here, we show that protein glycosylation (N- and O-linked) was only minimally disturbed in SLC35A2-CDG patient-derived fibroblasts. However, lipid glycosylation was significantly impaired, with accumulation of glucosylceramide and deficiency of digalactosylated glycosphingolipids (GSLs) and complex gangliosides. Galactose supplementation increased UDP-galactose, its transport into the Golgi, and improved deficient GSL synthesis through direct incorporation of the provided galactose. This improved GSL homeostasis in all patient-derived fibroblasts and in another SLC35A2 deficient cell model (CHO-Lec8). Additionally, SLC35A2-CDG serum analysis identified hydroxylated GSLs, particularly GM3, as potential disease biomarkers. Given the essential role of gangliosides in central nervous system function, their deficiency is likely a key factor in the neurological involvement of this disorder. These findings pave the way for new nutritional therapies with GSL supplements and highlight the importance of studying lipid glycosylation to better understand the complex pathophysiology of CDG.